SEMIOTIC ANALYSIS OF ROLAND BARTHES ON THE POSTER OF THE FILM WOMEN FROM ROTE ISLAND - Muhammad Noza; Sri Seti Indriani; Aceng Abdullah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to analyses the visual meanings in the film poster Women from Rote Island by Jeremias Nyangoen using Roland Barthes’ semiotic analysis. As a medium of visual communication, the film poster is understood not only as a promotional tool but also as a representation of the social experiences of women survivors of violence. This research employs a qualitative descriptive method with the official theatrical poster of Women from Rote Island as the main object of analysis. The analysis is conducted at three levels of meaning namely denotation, connotation and myth focusing on visual and verbal elements such as the chained woman lying on the floor, the dominance of dark colours, the typography, the row of festival awards and the screening information. The findings show that the poster constructs a powerful image of women’s bodies as bound by violence, trauma and unequal power relations, while simultaneously offering a critique of patriarchal culture and the normalization of sexual violence. The poster also positions the voices of women from peripheral regions as legitimate and important narratives within the public sphere through the medium of film, thereby contributing to the enrichment of studies on visual meaning in film posters, particularly in the context of the representation of women and gender-based violence in Indonesia. Keywords: semiotics, roland barthes, film poster, visual meaning, women from rote island.